MODEL PREDATOR-PREY MENGGUNAKAN RESPON FUNGSIONAL TIPE II DENGAN PREY BERSIMBIOSIS MUTUALISME - Ahmad Nasikhin; Niken Larasati (Jurnal Ilmiah Matematika dan Pendidikan Matematika (JMP), 2013)
In this paper, we study the dynamic behavior of predator-prey model using functional response type II and symbiotic mutualism of prey. One of the six equilibrium points is the coexistence point which is asymtotically stable. In this point, the number of prey and predator for a long term depends on the interaction level of prey to another species and the interaction level of another species to prey.